Unsupervised online constructed-response tests: Maximising student learning and results integrity - Johnson, Genevieve; Davies, Sharon (Australasian Society for Computers in Learning in Tertiary Education, 2012)
This paper reports a case study in which the Blackboard essay test tool was used to evaluate e-student learning. To promote student learning as well as maintain the integrity of test results, constructed-response items were randomly selected from a large pool of study questions and the time available to complete the tests was limited. The e-lecturer maintained a reflective journal and the e-students were invited, via email, to provide feedback on their perception of the value of the testing approach used in their e-class. Overall, students evaluated the use of the online tests positively, although issues of technology difficulties presented challenges for some students. The e-lecturer was particularly positive about the benefits of such as approach to online assessment citing ease of test management including student test submission, provision of feedback and grading. Unsupervised online constructed-response tests have the potential to enhance student learning while providing valid test scores.